Correlations of insulin function with levels of adipocyte fatty acid-binding protein and serum uric acid in patients with newly diagnosed type 2 diabetes mellitus and abdominal obesity - Sun, Xueli; Sun, Xuefang (Progress in Nutrition, 2021)
Aim: To explore the correlations of insulin function with the levels of adipocyte fatty acid-binding protein (A-FABP) and serum uric acid (SUA) in patients with newly diagnosed type 2 diabetes mellitus (T2DM) with abdominal obesity. Methods: A total of 218 newly diagnosed T2DM patients were divided into abdominal obesity (n=98) and non-abdominal obesity groups (n=120) according to waist circumference. Their baseline clinical data, laboratory indices, A-FABP and SUA levels, homeostasis model assessment of insulin resistance (HOMA-IR) and HOMA-β were compared. The correlations of HOMA-IR with A-FABP, SUA levels and HOMA-β were subjected to Pearson’s analysis. The risk factors for IR were explored by logistic regression analysis. Results: The abdominal obesity group had significantly higher body mass index (BMI), waist circumference, waist-to-hip ratio, diastolic blood pressure and systolic blood pressure than those of non-abdominal obesity group (P<0.05). Compared with non-abdominal obesity group, the abdominal obesity group had higher levels of very low-density lipoprotein-cholesterol, low-density lipoprotein-cholesterol, triglyceride (TG), total cholesterol, aspartate aminotransferase, alanine aminotransferase and fasting serum insulin (P<0.05), and lower high-density lipoprotein-cholesterol level (P<0.05). The abdominal obesity group had higher HOMA-IR, HOMA-β and A-FABP, SUA levels than those of non-abdominal obesity group (P<0.05). HOMA-IR was positively correlated with A-FABP, SUA levels and HOMA-β (P<0.0001). BMI, waist circumference, as well as TG, A-FABP and SUA levels were risk factors for IR (P<0.05). Conclusion: In newly diagnosed T2DM patients with abdominal obesity, A-FABP and SUA levels significantly rise, being positively correlated with IR. Therefore, reducing lipids and weight together with controlling A-FABP and SUA levels may be important strategies for relieving IR and preventing T2DM complicated with abdominal obesity.